Investing in Malaysian healthcare using technique for order preference by similarity to ideal solution - Azhar, Farah Waheeda; Rahim, Zati Halwani Abd; Fahami, Norasyikin Abdullah; Abdul Rahim, Siti Khatijah Nor; Karim, Hilwana Abd (Institute of Advanced Engineering and Science, 2022)
The purpose of this research is to assess the financial performance of Malaysian Healthcare companies using the multi-criteria and decision-making method, namely technique for order preference by similarity to ideal solution (TOPSIS). The financial data of 20 companies in 2019 are retrieved from Datastream. For many years, ratios of financial aspects have been employed to analyse the companies’ financial performance. However, some studies indicate that the traditional ratio analysis is insufficient to measure a firm's financial performance. Thus, this paper employs the technique for order preference by similarity to ideal solution, or simply TOPSIS, to gain a more comprehensive result. The TOPSIS approach involves seven steps, utilizing significant ratios in financial aspect such as debt ratio, debt to equity ratio, current ratio, return on equity (ROE), acid-test ratio, earnings per share (EPS), and return on asset (ROA), as the criteria to evaluate the companies' financial performances. The result of this study ranks 20 healthcare companies in Malaysia and makes recommendations for investment-worthy companies to the investors, allowing the maximization of investment benefits. The results from this research are crucial for investors, companies, market participants, public and private policymakers to enhance their investment decision-making.